2011
DOI: 10.1111/j.1755-6686.2011.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Dietary Adherence in Patients With End‐stage Renal Disease

Abstract: Depressive symptoms may be associated with fluid and dietary non-adherence which could lead to poorer outcomes. The purpose of this study was to examine the relationship between depressive symptoms and fluid and dietary adherence in 100 patients with end-stage renal disease (ESRD) receiving haemodialysis. A descriptive, cross-sectional design with a convenience sample of 100 patients with ESRD receiving maintenance haemodialysis completed instruments that measured self reported depressive symptoms and perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
3
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 45 publications
7
92
3
6
Order By: Relevance
“…As part of the Dialysis Outcomes and Practice Patterns Study, Lopes et al demonstrated that among patients on chronic hemodialysis, depression was independently associated with increased mortality and hospitalization (15). Several other studies reported similar associations as well as lower medication and dietary adherence among patients on chronic hemodialysis with depression (16)(17)(18)(19)(20)(21)(22)(23)(24). Considerably less is known about the associations of pain with clinical outcomes, although a recent study found that interdialytic pain was associated with increased mortality (25).…”
Section: Introductionmentioning
confidence: 88%
“…As part of the Dialysis Outcomes and Practice Patterns Study, Lopes et al demonstrated that among patients on chronic hemodialysis, depression was independently associated with increased mortality and hospitalization (15). Several other studies reported similar associations as well as lower medication and dietary adherence among patients on chronic hemodialysis with depression (16)(17)(18)(19)(20)(21)(22)(23)(24). Considerably less is known about the associations of pain with clinical outcomes, although a recent study found that interdialytic pain was associated with increased mortality (25).…”
Section: Introductionmentioning
confidence: 88%
“…It is in fact, a worldwide epidemic health problem of increasing prevalence and expenditure [1]. It is a major health problem globally, casting an enormous burden on healthcare systems, is a source of psychological distress, and is associated with cardiovascular diseases, resulting in substantial morbidity and mortality [2]. According to the Global Burden of Disease Study, CKD was ranked 18 th in the list of causes of total number of global deaths in 2010 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian and international studies report high levels of depression, ranging from 25% to more than 60% of the studied samples (Nifa & Rudnicki, 2010;Khalil, Frazier, Lennie & Sawaya, 2011;Turkmen et al, 2012;Ossareh, Tabrizian, Zebarjadi & Joodat, 2014).…”
Section: Introductionmentioning
confidence: 99%